Profile Of Tezacaftor/Ivacaftor Combination And Its Potential In The Treatment Of Cystic Fibrosis [Erratum] - Shiferaw D; Faruqi S (Dove Medical Press, 2019)
Shiferaw D, Faruqi S. Ther Clin Risk Manag. 2019;15:1029–1040.Following a review of our paper post-publication, we found an error had been introduced during the typesetting process.On page 1029, the first sentence of the introduction section reads as “Cystic fibrosis (CF) is a life-threatening genetic disease that affects approximately ct 380,000 people worldwide.1” This should read as “Cystic fibrosis (CF) is a life-threatening genetic disease that affects approximately 80,000 people worldwide.1”Read the original article